Evaluating the effects of the Home Affordable Modification Program - Cóndor, Richard (Banco de México, 2021)
The Home Affordable Modification Program (HAMP) was a loan modification program introduced in 2009, in the U.S., to assist highly indebted homeowners with avoiding foreclosure. This program also encouraged private lenders to offer more sustainable modifications. This paper studies the role of HAMP in preventing higher foreclosures rates during and after the Great Recession, in the context of a general-equilibrium heterogeneous-agents model with two types of households (Borrowers and Savers), uninsurable idiosyncratic risk, and both private and HAMP modifications. The main result is that, without HAMP, the peak in the foreclosure rate could have been 50% larger (3.2 percent vs 2.2 percent in data).
10419/240717
Keywords: Graue Literatur; Housing policy; Heterogeneous agents; Financial Economics